The Influence of Islamic Values on Students’ Ethical Awareness - Sofiatus Zahriyah (AT-TAKILLAH : Jurnal Pendidikan dan Keislaman, 2026)
This study aims to analyze the influence of Islamic values on students’ ethical awareness in schools. Ethical awareness is an important aspect of students’ moral development because it helps individuals distinguish between right and wrong and encourages responsible behavior in social life. In the modern era, many students face ethical challenges caused by globalization, technological advancement, peer pressure, and social media influences. Therefore, Islamic values are considered important in guiding students to develop positive moral attitudes and ethical behavior. This research employed a quantitative approach using a survey research design. The population of the study consisted of students at a selected school, while the sample was determined using purposive sampling techniques. Data were collected through questionnaires, observations, and documentation. The questionnaire used a Likert scale to measure students’ perceptions regarding Islamic values and ethical awareness. The collected data were analyzed using descriptive statistics and simple linear regression analysis. The findings revealed that Islamic values have a positive and significant influence on students’ ethical awareness. Students who actively practiced Islamic values demonstrated better honesty, discipline, responsibility, empathy, and respect toward others. Teachers, school environments, and religious activities also contributed significantly to strengthening students’ ethical behavior and moral understanding. However, several challenges such as negative social influences, low learning motivation, and limited innovation in teaching methods were still identified. Therefore, schools are encouraged to improve Islamic Religious Education learning through interactive teaching strategies, technology integration, and stronger collaboration among teachers, parents, and communities. Overall, this study concludes that Islamic values play an essential role in strengthening students’ ethical awareness and developing responsible individuals with positive moral character in modern society.